2004
DOI: 10.1093/treephys/24.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regulated deficit irrigation during the pre-harvest period on gas exchange, leaf development and crop yield of mature almond trees

Abstract: We investigated the effects of regulated deficit irrigation (RDI) during the pre-harvest period (kernel-filling stage) on water relations, leaf development and crop yield in mature almond (Prunus dulcis (Mill.) D.A. Webb cv. Cartagenera) trees during a 2-year field experiment. Trees were either irrigated at full-crop evapotranspiration (ETc=100%) (well-irrigated control treatment) or subjected to an RDI treatment that consisted of full irrigation for the full season, except from early June to early August (ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 35 publications
4
29
0
7
Order By: Relevance
“…^pd on 31 July 2002 was higher on the Drepanoto and GN-22 than on the remaining rootstocks. Common levels of ^pd of almond trees grown under irrigation were maintained above -1.0 MPa whereas ^pd was significantly lower in non-irrigated trees (<-2 MPa) than in irrigated ones (Romero et al 2003). ^pdOf almond trees maintained in a growth chamber at 90, 60, and 30% of available water decreased from -1.1 to -1.2 and -2 MPa respectively (Dettori 1987).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…^pd on 31 July 2002 was higher on the Drepanoto and GN-22 than on the remaining rootstocks. Common levels of ^pd of almond trees grown under irrigation were maintained above -1.0 MPa whereas ^pd was significantly lower in non-irrigated trees (<-2 MPa) than in irrigated ones (Romero et al 2003). ^pdOf almond trees maintained in a growth chamber at 90, 60, and 30% of available water decreased from -1.1 to -1.2 and -2 MPa respectively (Dettori 1987).…”
Section: Resultsmentioning
confidence: 88%
“…This tolerance is conferred from the rootstock to the scions (Massai & Gucci 1997) and therefore, where water for irrigation is not available, selection of rootstocks more tolerant to water stress than 'Ferragnès' is considered critical for tree survival and good performance. Adaptation of a rootstock to water stress may involve maintenance of high photosynthetic rate and stomatal conductance, a decrease of transpirational water loss, and a reduction of growth of the tree (Romero et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, under the addition of 3 mg Se L -1 , Ca has followed the same pattern as the other macro-nutrients, while Mg had no significant difference in its concentration. Water treatment could affect the nutrient balance in plants (Romero et al, 2004). Its combination with Se addition at various levels could have contrasting effects on nutrient uptake.…”
Section: Effect Of Water Treatmentmentioning
confidence: 99%
“…Strong positive linear relationships were detected between g s , A, and E in our study as similarly observed for mature almond (Prunus dulcis (Mill.)) trees (Romero et al, 2004). In contrast, water deficits may decrease A directly by affecting the metabolic and photochemical process in the leaf or indirectly through stomatal closure leading to cessation of leaf growth and consequent decreased leaf area.…”
Section: Seedling Physiological and Morphological Responses To Droughtmentioning
confidence: 99%